Lettere di Giulio Perticari a Gian Giacomo Trivulzio - Brambilla, Simona (Verbum – Analecta Neolatina, 2015)
The study provides the critical edition of ten letters written by Vincenzo Monti's son-in-law, Giulio Perticari to Gian Giacomo Trivulzio from October 3rd 1813 to October 2nd 1820. The letters are preserved in the Biblioteca Trivulziana in Milan. The letters are preceded by an introduction, describing their contents, which are in great part related to manuscripts, ancient editions and many literary works, including lyrics by Poliziano, Fazio degli Uberti's Dittamondo, some manuscripts and ancient editions of the Passione by Niccolò di Mino Cicerchia, and works by Dante.